2017
DOI: 10.1021/acs.jpcb.7b06967
|View full text |Cite
|
Sign up to set email alerts
|

Pauli Repulsion Versus van der Waals: Interaction of Indenocorannulene with a Cu(111) Surface

Abstract: Modification of metal electrode surfaces with functional organic molecules is an important step toward organic electronics. The interaction of the buckybowl indenocorannulene with a Cu(111) surface and the two-dimensional self-assembly on the same surface was studied by means of scanning tunneling microscopy and dispersion-enabled density functional theory. Based on the conjecture of maximizing van der Waals interaction with the surface one would expect the indeno group to be aligned parallel to the surface. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…A depletion in the molecule at 17 Å causes a mirror charge (accumulation) at 13 Å, for example (Figure b). Similar values have been reported (theoretically and experimentally) for 1 , pentamethyl‐ 1 , and 3 on Cu(111) . The polarization binding mechanism of adsorption has been described previously for benzene on coinage metals .…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…A depletion in the molecule at 17 Å causes a mirror charge (accumulation) at 13 Å, for example (Figure b). Similar values have been reported (theoretically and experimentally) for 1 , pentamethyl‐ 1 , and 3 on Cu(111) . The polarization binding mechanism of adsorption has been described previously for benzene on coinage metals .…”
Section: Resultssupporting
confidence: 87%
“…The D‐DFT calculations yield a strong binding of 5.7 eV for 2 , which is substantially larger than that calculated for 3 . D‐DFT calculations for 3 on Cu(111) also showed that the single indeno group was not perfectly parallel to the surface plane, indicating a binding to the surface at the bowl and not by maximal vdW contact to the surface through the benzene indeno tab …”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations